The Emergence of Cognitive Maps for Spatial Navigation in 7‐ to 10‐Year‐Old Children. Issue 3 (8th July 2019) - Burles, Ford; Liu, Irene; Hart, Chelsie; Murias, Kara; Graham, Susan A.; Iaria, Giuseppe
Abstract : Although much is known about adults' ability to orient by means of cognitive maps (mental representations of the environment), it is less clear when this important ability emerges in development. In the present study, 97 seven‐ to 10‐year‐olds and 26 adults played a video game designed to investigate the ability to orient using cognitive maps. The game required participants to reach target locations as quickly as possible, necessitating the identification and use of novel shortcuts. Seven‐ and 8‐year‐olds were less effective than older children and adults in using shortcuts. These findings provide clear evidence of a distinct developmental change around 9 years of age when children begin to proficiently orient and navigate using cognitive maps.